Analysis of coaches’ perception of the impact of their stress on the coach-athlete relationship - Balore, Julibert Jr Noynoyan; Fueyo, Jona; Rubio, Aaron; Hernández, Adelina Martins (Universitas Tanjungpura, 2026)
Background. The coach–athlete relationship is one of the most influential drivers of performance, motivation, and health within sporting environments. But the nature of this regard is heavily conditioned by the stress that attends on coaches, which can influence how they behave and communicate, and their ability to offer appropriate support. Objectives. The purpose of this study was to investigate how coaches experience that their stress affects the interaction and the relation quality with athletes. Methods. Using a qualitative research design, semi-structured interviews were conducted with thirteen coaches from various sports and institutional backgrounds. Participants were selected using purposive sampling. Thirteen coaches took part in one-on-one interviews conducted via Google Meet. The sample included coaches from both public and private schools who were actively involved in coaching at different levels of competition, such as international, national, and Palarong Pambansa events. The data were analyzed using Braun and Clarke’s (2006) thematic analysis approach, aided by NVivo 14 software. Results. Three primary stress sources emerged: role-related, relational, and contextual/external. These stressors led to negative outcomes, including controlling or hostile coach behaviors, impaired communication, and role overload leading to athlete neglect. Despite these challenges, coaches employed strategies such as coaching practices and relationship management, personal wellness behaviors, and institutional support. Conclusion. Findings show that coaching is a relational process influenced by stress and coping. Emotional regulation and interpersonal awareness are essential to coaching success. Institutional reforms and mental health resources are necessary to support coaches in managing stress and maintaining positive relationships. This research contributes to coaching psychology literature by emphasizing that coach support is critical to sustaining healthy coach-athlete dynamics and improving athletic outcomes.